The legitimacy of the nurse practitioner as a non-medical surgical assistant: Historical evidence from Australia. Issue 6 (December 2020) - Hains, Toni; Rowell, David; Strand, Haakan
ABSTRACT: Problem: The Non-Medical Surgical Assistant role has been practised in Australia for over 30 years. Despite this, the role remains unregulated, and government policy does not offer a rebate for the private surgical patient when the surgical assistant is not a Medical Practitioner. Aim: To investigate the legitimacy; as outlined by Donabedian; of the Nurse Practitioner performing the role of the surgical assistant in Australia. Methods: Examination of peak professional bodies' guidelines, opinions of other service providers, Australian Government policy and the Australian law. Findings: While not reflected in Government policy, the Nurse Practitioner is a legitimate and lawful provider of intraoperative surgical assisting care in Australia. Discussion: The Medical Benefits Schedule does not reflect contemporary, evidence-based practise or the law concerning the Nurse Practitioner undertaking the role of a surgical assistant, this causes the patient an out of pocket expense or reduced access to care. Conclusion: The Australian Nurse Practitioner is a legitimate and lawful provider of these services.